PERKEMBANGAN DAN PENGARUH PEMIKIRAN TEOLOGI MU‘TAZILAH TENTANG KEMAKHLUKAN AL-QUR’ĀN TAHUN 124-218 H/742-838 M - . Jamaluddin (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2015)
This paper examines the development and influence of the thoughtof the created al-Qur’ān of the Mu’tazilite theology years 124-218 AH / 742- 833 AD. The thougth of the created al-Qur’ān that occurred for the first time appeared during the Umayyad Daulah, gaining momentum of its development when received and distributed by the Mu’tazilite. This occurs because the close relations between the Mu’tazilite and the Caliph al-Mamun. The linkage between religious thought and government impact on the government’s strong support in spreading thought of the created al-Qur’ān. It is characterized by ideologization of the thought of the created al-Qur’ān officially by the state to the scholars and judges who were under the power Daula Abbasid, by running of the Miẖnah policy in 218 AH / 838 AD. After the year 218 AH / 838 AD, the influence of thought of the created al-Qur’ān is still quite strong both in the social, politic and culture.Keywords: al-Ma’mūn, Mu‘tazilite, the created al-Qur’ān, Miẖnah